Analisis Tingkat Keuntungan dan Risiko Sistematis Sebagai Dasar dalam Keputusan Investasi Pada Perusahaan Jakarta Islamic Index (JII) di Bursa Efek Indonesia (BEI) - Eva Rachmawati; Anita Syafariah; Rizki Lestari (Jurnal Ekonomi Manajemen Perbankan, 2022)
Risks that really must be considered are systematic risks, because those risks are faced by all companies. Stock analysis must be done carefully. Investors can choose various alternative options for companies that have high returns with certain risks or choose companies that have the smallest risk with certain benefits. The right investment decision is expected to provide optimal results. The method used in this research is descriptive method using a single index model (single index model).Investors can invest their funds in the basic industrial and chemical business sectors that have the highest level of profit and the Trade and Investment Services sector has the least systematic risk. The lowest value of the risk is owned by the Trade and Investment Service Company, thus investors can invest their funds in the Basic and Chemical Industry or in the Trade Services sector.Keywords: Profit Rate, Systematic Risk, and Investment Decisions.